2024
DOI: 10.2174/1573399819666230314093721
|View full text |Cite
|
Sign up to set email alerts
|

Can Polyherbal Medicine be used for the Treatment of Diabetes? - A Review of Historical Classics, Research Evidence and Current Prevention Programs

Abstract: Diabetes mellitus (DM), a chronic medical condition, has attained a global pandemic status over the last few decades affecting millions of people. Despite a variety of synthetic drugs available in the market, the use of herbal medicines for managing diabetes is gaining importance because of being comparatively safer. This article reviews the result of a substantial literature search on polyherbal formulations (PHFs) developed and evaluated with potential for DM. The accumulated data in the literature allowed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 511 publications
0
3
0
Order By: Relevance
“…Furthermore, research utilizing polyherbal extracts in diabetic rat models has shown positive outcomes, suggesting the potential efficacy of polyherbal tablets for diabetes management [ 3 ]. Examples like Kabasurakudineer demonstrate the synergistic effects of polyherbal formulations in treating metabolic diseases such as diabetes, emphasizing the significance of herbal remedies in addressing prevalent health issues [ 73 ]. The integration of traditional medicine into diabetes care highlights the necessity for further research and incorporation of herbal therapies into mainstream healthcare practices [ 74 ].…”
Section: Polyherbalism In the Management And Treatment Of Dmmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, research utilizing polyherbal extracts in diabetic rat models has shown positive outcomes, suggesting the potential efficacy of polyherbal tablets for diabetes management [ 3 ]. Examples like Kabasurakudineer demonstrate the synergistic effects of polyherbal formulations in treating metabolic diseases such as diabetes, emphasizing the significance of herbal remedies in addressing prevalent health issues [ 73 ]. The integration of traditional medicine into diabetes care highlights the necessity for further research and incorporation of herbal therapies into mainstream healthcare practices [ 74 ].…”
Section: Polyherbalism In the Management And Treatment Of Dmmentioning
confidence: 99%
“…Recent developments in this field include the creation and evaluation of polyherbal tablets derived from medicinal plants, showing promising results in diabetic rat models. The development of stable oral dosage formulations signifies progress in this area of research, offering new avenues for diabetes management [ 73 ]. Collaboration between traditional healers, researchers, and healthcare practitioners is essential for unlocking the full benefits of polyherbalism in diabetes care while safeguarding indigenous knowledge for future generations.…”
Section: Polyherbalism In the Management And Treatment Of Dmmentioning
confidence: 99%
“…It is expected to rise exponentially to 300 million people in the next two decades[ 2 ] or 439 million by 2030[ 3 ]. The predicted increase in the number of diabetic cases by Shaw et al [ 3 ] has been reached in just eight years, which was actually expected to occur over a span of 20 years[ 4 ]. Additionally, every year, nearly 400 million people suffer from DM and around 1.6 million people die from it; the vast majority of them are from low-income families[ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%